2014
DOI: 10.1001/jamainternmed.2014.1315
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Physician Partner Program on Physician Efficiency and Patient Satisfaction

Abstract: Drs Reuben and Koretz had full access to all the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 4 publications
(4 reference statements)
3
24
0
Order By: Relevance
“…One study found that 3 geriatric physicians practicing in a similar model had shorter visit times; however, the time the provider spent communicating with patients was not measured. 8 The same model did not decrease duration of 2 internists' visit times, but did reduce previsit and after-visit work. 8 Another study found that scribe use decreased one cardiologist's time in the room but increased direct physician-patient interaction, without affecting patient satisfaction.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One study found that 3 geriatric physicians practicing in a similar model had shorter visit times; however, the time the provider spent communicating with patients was not measured. 8 The same model did not decrease duration of 2 internists' visit times, but did reduce previsit and after-visit work. 8 Another study found that scribe use decreased one cardiologist's time in the room but increased direct physician-patient interaction, without affecting patient satisfaction.…”
Section: Discussionmentioning
confidence: 92%
“…8 The same model did not decrease duration of 2 internists' visit times, but did reduce previsit and after-visit work. 8 Another study found that scribe use decreased one cardiologist's time in the room but increased direct physician-patient interaction, without affecting patient satisfaction. 9 The results of our work confirm that physicianpatient interaction time can be improved by a team-based model.…”
Section: Discussionmentioning
confidence: 92%
“…Team documentation has been associated with greater physician and staff satisfaction, improved revenues, and the capacity of the team to manage a larger panel of patients while going home earlier. 33,34 • Use pre-visit planning and pre-appointment laboratory testing to reduce time wasted on the review and follow-up of laboratory results…”
Section: Addressing the Fourth Aimmentioning
confidence: 99%
“…Similarly, the addition of a Physician Partner, who acted as a scribe and performed administrative duties in a medical clinic led patients to report high satisfaction by increasing the amount physician contact. 31 Guss and colleagues 32 implemented a telephone call to patients after discharge from the emergency department in an effort to improve patient satisfaction. Patients who received a post-discharge phone call were more likely to recommend the hospital compared with those who did not receive a phone call (89% vs 56%).…”
Section: Additional Patient and Hospital Factors That Influence Patiementioning
confidence: 99%